Karakterisasi Morfometrik dan Jarak Genetik Rumpun-Rumpun Kelinci di Jawa Barat (MORPHOMETRIC CHARACTERIZATION AND GENETIC DISTANCE OF RABBIT BREEDS IN WEST JAVA) - Iskandar, Rudi Dedi; Brahmantiyo, Bram; Priyanto, Rudi (Jurnal Veteriner, 2017)
The objectives of this study were to assess morphometric characteristics, breeds relationship andvariables that distinguished among breeds of rabbits raised in West Java. This research used 419 rabbitsconsisted of Angora (AG), Dutch (DT), Flemish Giant (FG), Lop (LP), Netherland Dwarf (ND), Composite(PX), Rex (RX), Satin (ST), Reza (XA) and New Zealand White (ZW). Head length (PK), head width (LK), earlength (PTL), ear width (LTL), chest width (LD), chest depth (DD), chest circumference (LKD), body length(PB ), hips width (LP), length of the scapula bone (PS), humerus length (PH), radius-ulna length (PRU),femur length (PF) and tibia length (PT) were observed. Data were analyzed with analysis of variance,discriminant and canonical analysis using SAS program ver. 9.1.3 and MEGA5 program to get theconstruction of phenogram tree. FG and ST rabbits were generally larger in size and shape than the otherrabbits breeds, while ND rabbit had the smallest morphological size than other rabbits breeds, except forLK, LD and DD. Results of discriminant analysis showed that LP, RX, ND and XA had a high similarityvalue, otherwise DT, FG, ST, PX, AG and ZW had no the value. The closest genetic distance matrix valueindicated by PX-ZW breeds (1,53) and the farthest genetic distance indicated by FG-ND breeds (6,62).Phenogram tree construction showed that the breeds rabbits divided into five clusters, namely cluster ND,DT; ST clusters; FG cluster; cluster LP, PX, ZW and cluster AG, XA, RX. Phenotypic size that had stronginfluence on the differentiation of rabbit breeds were PTL, LTL, PRU, PH and PF on the canonical 1 alsoPT and PS on canonical 2.
Keywords: morphometric characteristics; genetic distance; rabbit breed